SISTEM AKUNTANSI PENGGAJIAN INDUK PEGAWAI DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA SURAKARTA - Sri Laksmi Pardanawati (ITB AAS INDONESIA, 2022)
This study aims to determine the main employee payroll system at the Surakarta State Treasury Service Office and to get a further description of the employee master payroll system applicable at the Surakarta State Treasury Service Office. The method used is the method of interview, observation, documentation, and literature study. The results of this study can be concluded that the Main Employee Payroll System at the Surakarta State Treasury Service Office has not been properly and properly authorized because it has not separated the 3 accounting functions, namely operational functions, storage functions, and accounting functions, which are still concurrently with the Expenditure Treasurer Section. As well as employees who work there are still concurrently in other parts.